PENGEMBANGAN MODUL KESIAPSIAGAAN GEMPA BUMI PADA MATERI GEOGRAFI UNTUK MENINGKATKAN KESIAPSIAGAAN SISWA SMAN 5 BANDA ACEH - Fitrissani .; Sri Adelila Sari; Sri Milfayetty; M. Dirhamsyah (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2014)
Abstract: The aim of this study to improve the preparedness of students of SMAN 5 Banda Aceh to the earthquake. The methods of research and development (research and development ) was used the model of Dick and Carey. The samples in this study is purposive sampling that class X - 3 as many as 25 students. Data was collected using a questionnaire that aims to look at cognitive, affective and psychomotor students , assessment questionnaire module Earthquake Preparedness (KGB), observation sheets learning process and outcome evaluation of student learning. Data analysis technique used is quantitative descriptive analysis. This study resulted in the KGB module. The results of the assessment in the form of modules scored 80. 7. This proves that the developed modules can be used to improve preparedness class X - 3 SMAN 5 Banda Aceh in the face of the earthquakeKeywords: Development, learning device, Dick and Carey model, geography, earthquake, preparedness